Clinical and Laboratory Findings of Normal Children Suspected of Having Cardiac Disease - Sudigdo Sastroasmoro; Nuraini Irma Susanti (Indonesian Pediatric Society, 1998)
The definite diagnosis of cardiac disease in infants and children usuallycannot be made on the clinical evidence alone; in most instances supportingexaminations are required. lt is understandable, therefore, that non-cardiologists might suggest that normal subjects are thought to have cardiac problems; the reverse is also true: infants and children with cardiac disease may be ignored. This study aimed to examine the clinical and laboratory findings of normal infants and children who were initially suspected to have cardiac disease. Of 3601 patients referred to our OPD of the Division of Cardiology, Department of Child Health, Medical School, University of Indonesia, from January 1983 to December 1992; in 1782 patient (49.5%) no cardiovascular problems were detected. Most of them (66.2%) were of the age of less than 1 month. Most of the referring physicians (66.3%) were general practitioners. The referring diagnoses were congenital heart disease (286), cardiomegaly (197), rheumatic fever or rheumatic heart disease (110), and syndromes with cardiac involvement (104). The diagnoses were based on dyspnea, cyanosis on crying, chest pain, joint pains, and easy fatiguability. Murmurs found on examination were systolic in 355 patients (19. 9%), and continuous in 6 patients (0,33%). No diastolic murmurs were noted. The final diagnoses were normal (including innocent murmurs and sinus arrhythmias) in 85.8%, mild cardiomegaly in 10.4%., breath holding spells in 2.0%, sinus tachycardia in 0.9%, polyarthritis in 0.2% and other in 0.7% of all cases. More practice in cardiac physical examination is needed for medical students to reduce the unnecessary referrals.